Aryl hydrocarbon receptor antagonism and its role in rheumatoid arthritis - Nguyen, Nam Trung (J Exp Pharmacol, 2015)
Although rheumatoid arthritis (RA) is the most common autoimmune disease, affecting approximately 1% of the population worldwide, its pathogenic mechanisms are poorly understood. Tobacco smoke, an environmental risk factor for RA, contains several ligands of aryl hydrocarbon receptor (Ahr), also known as dioxin receptor. Ahr plays critical roles in the immune system. We previously demonstrated that Ahr in helper T-cells contributes to development of collagen-induced arthritis, a mouse model of RA. Other studies have shown that cigarette smoke condensate and pure Ahr ligands exacerbate RA by altering bone metabolism and inducing proinflammatory responses in fibroblast-like synoviocytes. Consistent with these findings, several Ahr antagonists such as α-naphthoflavone, resveratrol, and GNF351 reverse the effect of Ahr ligands in RA pathogenesis. In this review, we summarize the current knowledge of Ahr function in the immune system and the potential clinical benefits of Ahr antagonism in treating RA.